Consciência moral e pós-modernidade: discernir, decidir e agir à luz de uma ética das virtudes - Almeida, André Luiz Boccato de (2010)
The initial point of this dissertation is, in the first place, to analyze the postmodernity with its implications on moral conscience. The complex postmodernity reality takes us to rethink the problems concerning conscience to beyond the traditional paradigms making us to think of an (a type of) ethic of virtues which grants us a triple challenge: to discern, to decide and to act amongst ethical relativisms and fundamentalisms. For this purpose, we emphasize a panoramic view of postmodernity with its theoretical and anthropological challenges, generators of a new culture and value opposing to the whole Christian anthropology. The moral conscience, discernment stage, decision and action of the human being, feeling this opposition, is called to rethink its deeper structure. For this purpose, we have passed a look over the Christian tradition of conscience accentuating the major biblical, theological and historical themes under it. It emphasizes the positive comprehension of the council present in Gaudium et Spes , nº 16, we stress its concise and coherent importance to the moral-theological reflection. We propose an ethic of virtues looking at the old ethical paradigms, but aiming the contemporary human subject who lives a crisis of sense, history and acting. Finding himself fragmented and ethically confuse in front of the countless ethical proposals, seductive and ephemeral, we want to show that an ethic of virtues is profoundly pedagogical and evangelical when to this human subject offers means to form and educate his conscience. Rescuing the theological and cardinals virtues under the stimulating and creative inspiration of St. Thomas, we want to present ways capable of generating the humanization and integration of the postmodern human subject. It is up to the human subject to form his conscience with creativity in an open-minded spirit by the discernment to decide and act in times of ethical relativisms and fundamentalisms, proposing to himself and to his environment a beyond of moralisms and immoralisms